Critical Discourse Analysis Fairclough on The Content of Game FF and PUBG in The Media Tiktok - Bayu Aji Sastra Jendra (CIC Lembaga Riset dan Konsultan Sosial, 2021)
A media that can connect every human being in all corners of the world so that it creates a new world, namely the online or virtual world. From here it is very possible for an exchange of ideology to occur through a discourse carried by an individual or a group which could be through a content channeled through a medium such as Tiktok for example. The purpose of this research is to analyze critical discourse on the contents in Tiktok media related to FF and PUBG games. The research method used is qualitative with a critical paradigm as a foundation in the point of view used. The theory used in this study is Norman Fairclough's critical discourse analysis with descriptive analysis, interpretation and explanation methods. The result of this research is the discovery of differences in discourse that are raised in each content in Tiktok media, where each content framing is carried out with the characteristics of each individual, so that the meaning of the discourse raised can be known by the general public.